Two rural development strategies organization, administrative performance and political priorities in India and Malaysia - Mauzy, Diane K. (Philippine Journal of Public Administration, 1975)
This essay will be a comparative retrospective analysis focusing on three aspects of two specific strategies within the rural development programs, mid-1950s to mid-1960s, of India and Malaysia.